Enhanced Magneto‐optical Properties of Semiconductor EuS Nanocrystals Assisted by Surface Plasmon Resonance of Gold Nanoparticles. Issue 43 (18th September 2013) - Kawashima, Akira; Nakanishi, Takayuki; Shibayama, Tamaki; Watanabe, Seiichi; Fujita, Koji; Tanaka, Katsuhisa; Koizumi, Hitoshi; Fushimi, Koji; Hasegawa, Yasuchika
Abstract Remarkable magneto‐optical properties of a new isolator material, that is, europium sulfide nanocrystals with gold (EuS–Au nanosystem), has been demonstrated for a future photo‐information technology. Attachment of gold particles that exhibit surface plasmon resonance leads to amplification of the magneto‐optical properties of the EuS nanocrystals. To construct the EuS–Au nanosystems, cubic EuS and spherical Au nanocrystals have been joined by a variety of organic linkers, that is, 1, 2‐ethanedithiol (EDT), 1, 6‐hexanedithiol (HDT), 1, 10‐decanedithiol (DDT), 1, 4‐bisethanethionaphthalene (NpEDT), or 1, 4‐bisdecanethionaphthalene (NpDDT) . Formation of these systems was observed by XRD, TEM, and absorption spectra measurements. The magneto‐optical properties of the EuS–Au nanosystem have been characterized by using Faraday rotation spectroscopy. The Faraday rotation angle of the EuS–Au nanosystem is dependent on the Au particle size and interparticle distance between EuS and Au nanocrystals. Enhancement of the Faraday rotation of EuS–Au nanosystems was observed. The spin configuration in the excited state of the EuS–Au nanosystem was also investigated using photo‐assisted electron paramagnetic resonance.